The Cambridge introduction to travel writing - Youngs,Tim (Cambridge University Press, 2013., 2013)
"Critics have long struggled to find a suitable category for travelogues. From its ancient origins to the present day, the travel narrative has borrowed elements from various genres - from epic poetry to literary reportage - in order to evoke distant cultures and exotic locales, and sometimes those closer to hand. Tim Youngs argues in this lucid and detailed Introduction that travel writing redefines the myriad